Geotechnical Design of the Luis Antonio Eguiguren Bridge Foundation, Piura, Peru - Escalaya Advíncula, Miriam (2023)
This paper presents the Case Study of the Geotechnical Design for Luis Antonio Eguiguren Bridge Foundation, located on the Piura river, that connects the districts of Castilla and Piura. A description of the studies carried out and the methodology used in the design of the deep foundation are provided, consistent with the structural and geological-geotechnical conditions, and the regional seismicity. The ultimate axial load capacity was evaluated, the allowable load capacity of the piles was determined based on an appropriate safety factor and the prediction of individual and group pile settlements is made. The verification of the load capacity was carried out through the dynamic load test. Likewise, the importance of the use of geophysical surveys is highlighted, mainly MASW (Method of Multichannel Analysis of Surface Waves) in the analysis and design of foundations.